Pengaruh Keaktifan Berorganisasi Siswa Di Sekolah Terhadap Motivasi Belajar Siswa Kelas X Dan Xi Sekolah Menengah Atas Negeri 1 Kartasura Tahun Ajaran 2015/2016 - Iskandar, Resya; , Drs. Djumali, M.Pd (2016)
The purpose of this study was to determine the influence of organizational activity of students in schools to motivate students of class X and XI SMA Negeri 1 Kartasura the academic year 2015/2016. This research includes quantitative research through the analysis of statistical inference. The population in this study were all students of class X and XI SMA Negeri 1 Kartasura join the organization. Samples taken as many as are 75 students with simple random sampling technique. Necessary data obtained through questionnaires and documentation. The questionnaire was previously tested the validity and reliability were tested. Data analysis technique used is simple linear regression analysis, t test. The results of the regression analysis obtained regression equation: Y = 4.163 + 0,338X. This equation shows that the motivation to learn is influenced by the activity of the organization. The conclusions drawn are: The active participation of students in the school to organize a positive effect on the motivation of students of class X and XI SMA Negeri 1 Kartasura the academic year 2015/2016 can be accepted. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 2.671> 2.000 and the significance value <0.05, namely 0.009.